Diagnostic validity of biomarkers in Parkinson's Disease: systematic review and meta-analysis - Maria Fernanda Baeta Neves Alonso da Costa; Emilene Reisdorfer; Silvana Silveira Kempfer; Gisele Cristina Manfrini Fernandes; André Luís Porporatti; Graziela De Luca Canto
ABSTRACT Objective: To identify biomarkers for Parkinson's disease, cerebrospinal fluid, blood, saliva, and urine. Method: The studies were collected from the Cochrane, LILACS, PubMed, SCOPUS, WEB OF SCIENCE, OpenGrey, ProQuest and Google Scholar databases starting from May 3, 2016 and updated on March 20, 2017. Twenty-two studies were evaluated, by the Quality Assessment Tool for Diagnostic Accuracy Studies and Review Manager 5.3. Results: Evidence shows that serum antibodies can be used as highly specific and accurate biomarkers for the diagnosis of Parkinson's disease at the outset. Biomarkers in the cerebrospinal fluid are related to increased motor severity, postural instability, gait abnormality, and cognitive impairment. Conclusion: Serum and cerebrospinal antibodies can be used as diagnostic biomarkers at the onset of the disease.